INVESTIGATING PLURILINGUAL AND PLURICULTURAL COMPETENCE ​​IN FOREIGN LANGUAGE TEACHING AT ISLAMIC BOARDING SCHOOL - Mahmud; Wirabhakti, Agus; Aisyah, Aisyah; Nailah Alya Faizah; Firmansyah (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to investigate teachers' pluricultural and plurilingual competencies in foreign language teaching at the Islamic boarding school. The field research method was conducted by using qualitative and quantitative approaches. The Qualitative Data aims to explore descriptive information about teachers' perception of the pluricultural and plurilingual competence in foreign language teaching at Islamic boarding school. While the quantitative approach aims to determine research results statistically. The subjects of this research were foreign language teachers at Islamic boarding schools in several regions in Indonesia. The Instruments of the research consisted of questionnaires and interviews. Data is collected through distribution virtual questionnaire using Google Form. Statistical questionnaire data using score calculations using the T x Pn formula. The Interpretation results of the data statistically shows that foreign language teachers' perceptions of Pluricultural competency is concluded as good category because it reach 67%. Meanwhile the percentage interpretation of foreign language teachers' perceptions of competence plurilingual is also in good category by 73%. it can be concluded that the foreign language teachers of the Islamic boarding school perceived good plurilingual and good pluricultural.